Healing and reincarnation: the "spiritual healing" process at Santo Daime - Greganich, Jéssica (2010)
This article aims to analyze the healing process in the Brazilian religion of Santo Daime in CEFLURIS (Eclectic Center of the Universal Flowing Light Raimundo Irineu Serra) based on the paradigm of embodiment proposed by Thomas Csordas (2008). Csordas states religious experience as a privileged setting to observe the relationship between embodiment and signification, launching the basis of a psychological anthropology which has been standing out by its phenomenological approach. In this sense the analysis presents an ethnographical description and a case study of the health/illness system of Santo Daime of healing/illness known as “spiritual healing”, that involves reincarnation and the ritual consumption of ayahuasca, as we can find in “Céu de São Miguel” church in the municipality of Picada Verão, next Porto Alegre, capital of Rio Grande do Sul State (Brazil).